Effectiveness of Utilizing Program Keluarga Harapan (PKH) in Nagari Tanjung Alai Solok Regency - Sari, Nur Vita; Putri, Siska Elasta (Indev: Literasi Media Dakwah dan Pengembangan Masyarakat, 2025)
The main problem in this thesis is the effectiveness of the utilization of the Family Hope Program (PKH) funds in Nagari Tanjung Alai, District X Koto Singkarak, Solok Regency. The objectives of this discussion are to describe the process of PKH fund disbursement, explain the utilization of PKH funds, and assess the impact of PKH on its beneficiaries. The type of research used by the researcher is field research utilizing qualitative research methods through a descriptive analysis approach to gather data related to the researched issues. Data collection techniques employed include observation, interviews, and documentation. This study utilizes both primary and secondary data sources. Data analysis techniques involve data collection, data reduction, data presentation, and verification, followed by drawing conclusions. To ensure data validity, the researcher employs triangulation of sources, techniques, and time. From the field research conducted, it can be concluded that the disbursement process of the Family Hope Program (PKH) consists of three stages: beneficiary data collection, beneficiary data selection, and fund disbursement stages. The PKH disbursement process generally proceeds smoothly but encounters some obstacles. Beneficiaries utilize PKH funds according to the categories of components they receive. The positive impact includes transforming lives, improving family economies, and reducing household expenses. However, there are also negative impacts such as social jealousy, mismatches between recipients and PKH objectives, and instances of recipients becoming unmotivated to work.